An experimental evaluation of the scalability of permissioned blockchains - Tavonatti, Stefano; Battulga, Davaadorj; Farhadi, Mozhdeh; Caprini, Carlo; Miorandi, Daniele (2021 8th International Conference on Future Internet of Things and Cloud (FiCloud), 2021)
Permissioned blockchains are decentralized digital systems, which are used to record transactions and which maintain multiple, synchronized copies of the whole list of transactions (i.e., the ledger) on geographically dispersed nodes. Cryptographic operations are used to 'chain' transactions in the ledger, making the system tamper-resistant. In permissioned blockchains, access to the system (in particular in terms of the ability to append new transactions to the ledger) is limited to a specific set of well-identified nodes: this feature puts them apart from the blockchain systems ('permissionless') commonly use to power cryptocurrencies. The ability to control who can operate on the blockchain makes such systems a good choice for implementing use cases like supply chain management, business ecosystems or notarization. Driven by the interest in launching a new digital product for the education market (related to the management of education certificates), we faced some issues related to the scalability of permissioned blockchains. Given the lack of a consistent and comprehensive literature on the subject, we run an extensive experimental testing campaign on a large-scale distributed computing infrastructure (Grid'5000), measuring the performance of a popular permissioned blockchain framework (Hyperledger Fabric) under varying conditions. In this paper, we share the results obtained, which shed light on both scalability bottlenecks and possible approaches for overcoming such limitations in real-world business contexts.